Can We Talk About Race? Exploring Online Comments about Race-Related Shootings. Issue 1 (1st January 2020) - Masullo Chen, Gina; Fadnis, Deepa; Whipple, Kelsey
Abstract: A quantitative content analysis was conducted of online comments ( N = 1, 840) posted on news stories about 4 shooting deaths involving Black Americans and police officers to assess how Americans talk about race in the digital space. Findings showed that uncivil attributes, such as profanity or name-calling, were more frequent than deliberative attributes, such as using evidence to support one's point. Findings suggested there are scant but meaningful deliberative discussions about race in the comments we studied, but incivility mires that conversation. Results are discussed in terms of critical race theory and deliberative democracy.